PENGARUH BLENDED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH SISWA SMK DIPONEGORO SALATIGA - Sari, Rusnia Tri Prastika; Kriswandani, Kriswandani (LPPM Universitas Bina Bangsa, 2024)
The blended learning model is a learning model that uses 2 methods, namely face-to-face and visual, so that it can provide a comprehensive learning experience to students. The purpose of this research is to determine the effect of the Blended Learning Model on students' problem solving abilities. This type of research uses quasi-experimental research with a one group pretest and posttest research design by comparing pretest and posttest scores. The population of this study used Class The results of this research show that the significance value of the Wilcoxon Signed Rank Test is 0.028 <0.05, which means there is a significant difference between the pretest and posttest mean values. In other words, there is an influence of the Blended Learning Model on the problem solving abilities of Class X Students at Diponegoro Vocational School